2010
DOI: 10.3109/02656736.2010.486777
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic and necrotic effects of tumour necrosis factor-alpha potentiated with hyperthermia on L929 and tumour necrosis factor-alpha-resistant L929

Abstract: The results suggested that hyperthermia may enhance the necrotic and apoptotic effects of TNF-alpha on some tumour cells and overcome the resistance of some tumour cells to TNF-alpha.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…In this study, it was demonstrated that both CXCL12 (positive control) and activin A induced L929 cells migration, while TNF-α significantly inhibited L929 cells chemotaxis to activin A. Furthermore, inflammation declines the viability of fibroblasts to hinder the repair and regeneration of tissues, and it has been widely recognized that TNF-α inhibits L929 cells viability 34 , which was also confirmed in this study. Interestedly, activin A antagonized the inhibitory effect of TNF-α on L929 cells viability.…”
Section: Discussionsupporting
confidence: 82%
“…In this study, it was demonstrated that both CXCL12 (positive control) and activin A induced L929 cells migration, while TNF-α significantly inhibited L929 cells chemotaxis to activin A. Furthermore, inflammation declines the viability of fibroblasts to hinder the repair and regeneration of tissues, and it has been widely recognized that TNF-α inhibits L929 cells viability 34 , which was also confirmed in this study. Interestedly, activin A antagonized the inhibitory effect of TNF-α on L929 cells viability.…”
Section: Discussionsupporting
confidence: 82%
“…Hyperthermia is related to the inhibition of tumor growth and contributes to the enhancement of therapy against cancer. It is also related to tumor cell killing and the sensitization of these cells to radio and chemotherapy [ 178 , 179 ]. Tang et al studied the effect of hyperthermia on EMT, especially with Twist2, which is associated with EMT and metastases in HNSCC.…”
Section: Inhibition Of Emt Is Important In the Treatment Of Hnsccmentioning
confidence: 99%
“…In adults, elimination occurs primarily through glomerular filtration without the involvement of renal transporters, with 97% of the drug excreted unchanged in the urine. [21][22][23] Intact lisinopril, estimated to be…”
Section: Introductionmentioning
confidence: 99%
“…When taken during daytime, food does not appear to significantly affect its clinical efficacy. In adults, elimination occurs primarily through glomerular filtration without the involvement of renal transporters, with 97% of the drug excreted unchanged in the urine 21–23 . Intact lisinopril, estimated to be approximately 25–69% of the total dose, is excreted in the faeces as unabsorbed drug 22,24 …”
Section: Introductionmentioning
confidence: 99%